Identification of Numeracy Literacy Strategies in Elementary Schools: Implementation of Merdeka Curriculum - Wiryanto; Suryanti; M. Gita Primaniarta (Universitas Pendidikan Ganesha, 2025)
Strengthening 21st-century skills through numeracy literacy strategies is an essential requirement for realizing a student-centered learning process. The main challenge underlying this study is the inadequate integration of numeracy within instructional practices, which has hindered the optimal development of students’ competencies, particularly their problem-solving abilities. This research aims to analyze the implementation of numeracy literacy within the new learning paradigm and to explore its contribution to the development of student competencies. A qualitative approach using a phenomenological method was employed to examine the authentic experiences of teachers and students. The research subjects consisted of teachers and students from several elementary schools that apply a curriculum aligned with the Pancasila Student Profile. Data were collected through observations, interviews, and documentation, then analyzed using source triangulation and technique triangulation to ensure the validity of the findings. The results indicate that numeracy literacy plays a significant role in enhancing the quality of students’ competencies, encompassing both cognitive and socio-emotional aspects. Curriculum implementation facilitates the mapping of students’ abilities across six developmental phases through diagnostic assessments, which serve as the foundation for instructional planning. The study concludes that numeracy literacy programs are capable of strengthening students’ physical, social, affective, and academic competencies in a comprehensive manner. The implication of this research is the need for developing learning designs that are more integrative, adaptive, and sustainable in order to effectively support the achievement of 21st-century competencies.